The Predictors of Organizational Commitment: A Case Study of Private School Teachers in Pakistan - FAHEEM ULLAH QURESHI; DR. AQSA SIDDIQ; ABDUL MAJID; RUKHSAR (Journal of Business & Tourism, 2021)
The study investigates the impact of perceived organizational support, job involvement and job satisfaction on organizational commitment of teachers working in private sector schools of Peshawar, Pakistan. The sample (sample size N=100) of private school teachers in Peshawar was selected through random sampling technique. The data were collected via a structured and reliable questionnaire (α= 0.880) from the teachers and results were generated using SPSS software. The results proved that there is a positive correlation among the organizational commitment, perceived organizational support, job involvement and job satisfaction of the teachers serving in the private schools. In addition, the results of the multiple regression analysis support that teachers’ commitment has a significant relationship with their job involvement, perceived organizational support and job satisfaction at private schools in Peshawar. The results add new knowledge that can be used in both private and public sector schools of Pakistan to improve the organizational commitment of their teachers and to increase the motivation and retention level of the nation builders.